2014
DOI: 10.1002/adsc.201400027
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Synthesis of Oxetane Derivatives by Selective CH Activation

Abstract: The selective CA C H T U N G T R E N N U N G (sp 3 ) À H activation at position 2 in oxetanes has been accomplished by decatungstate photocatalysis under mild conditions. The resulting a-oxy radicals were trapped by electronpoor olefins resulting in the smooth preparation of 2-substituted oxetanes. The chemoselectivity in hydrogen abstraction in substituted oxetanes containing other H donating groups, such as CH 2 OH, CH 2 OAc and CHO, has been demonstrated in intramolecular models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Near-UV irradiation of DT gives rise to a singlet excited state that quickly decays to a more long-lived reactive intermediate (wO) capable of single electron transfer or HAT from aliphatic compounds. , Pioneering studies by Hill , demonstrated that alkane dehydrogenation, epimerization, and carbonylation can be readily affected using DT catalysis. Fagnoni, , Albini, Ravelli, , and Ryu ,,, have demonstrated that DT-promoted C­(sp 3 )–H abstraction can be coupled with several useful C–C, C–Si, and C–N bond-forming reactions. In addition, Noël and Orfanopolous , have studied alkane and alcohol oxidation by photoactivated DT.…”
Section: Introductionmentioning
confidence: 99%
“…Near-UV irradiation of DT gives rise to a singlet excited state that quickly decays to a more long-lived reactive intermediate (wO) capable of single electron transfer or HAT from aliphatic compounds. , Pioneering studies by Hill , demonstrated that alkane dehydrogenation, epimerization, and carbonylation can be readily affected using DT catalysis. Fagnoni, , Albini, Ravelli, , and Ryu ,,, have demonstrated that DT-promoted C­(sp 3 )–H abstraction can be coupled with several useful C–C, C–Si, and C–N bond-forming reactions. In addition, Noël and Orfanopolous , have studied alkane and alcohol oxidation by photoactivated DT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scope of this reaction was restricted to N -arylisoquinolines, since polymerizable or β-substituted acceptors proved less effective or unsuitable. Furthermore, Albini 9 and Fagnoni 10 reported a series of analogous reactions of α-oxy C–H bonds, but these reactions required the use of UV light, and only limited donor–acceptor combinations were applicable. Moreover, Fagnoni and Melchiorre reported the addition of dioxolanyl or α-amino radicals to iminium intermediates; however, this process was restricted to cyclic enones.…”
Section: Introductionmentioning
confidence: 99%
“…[23] However, at the present time, there are few synthetic methods that allow for the facile introduction of oxetane in a direct and routine fashion into medicinal agents. [23,24] We initially found that the use of this strained ring system led to an oxetanyl radical that underwent ring-opening polymerization under our optimal aqueous/acid conditions. Gratifyingly, when the coupling of oxetane and isoquinoline was carried out in MeCN (0.05 M) with the addition of ( n Bu) 4 NCl to help solubilize the persulfate anion, a useful 42% yield of the desired product was obtained (product 32 ).…”
mentioning
confidence: 99%